دراسة أثر المتغيرات الاقتصادية الكلية على مخاطر الائتمان في المصارف التجارية الخاصة العاملة في سورية باستخدام نموذج ARDL)) - العمار, رضوان; اسماعيل, زينة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aims to investigate the impact of macroeconomic variables on credit risks in the private commercial banks operating in Syria. Considering 10 commercial banks during 2009-2015, we study and analyze a number of macroeconomic variables proposed by the associated economic literature, and it seems that these variables have an important effect on credit risk. Preliminary tests are applied to test for the Stationarity of the selected variables. Besides, a (co-integrating) long-term relationship between the explanatory variables and the dependent variable is investigated using an ARDL model. A Fixed Effect panel model is fitted to assess the potential effects of the considered macro-variables on credits risks. It seems that macroeconomics variables have a significant role in explaining the changes in quality loans portfolio, which causes an increasing in the nonperforming loans in Syrian commercial banks. In effect, it results that there is a negative and statistically significant effect of both economic growth and inflation rate on credit risk, whereas, there is a positive and statistically significant effect of both real interest rate and real effective exchange rate on credit risk. هدف هذا البحث إلى دراسة أثر متغيرات الاقتصاد الكلي على مخاطر الائتمان في المصارف التجارية الخاصة العاملة في سورية. اعتماداً على بيانات نصف سنويّة من نوع بانل مؤلفة من 10 مصارف خلال الفترة 2009- 2015، تمّ دراسة وتحليل مجموعة من متغيرات الاقتصاد الكلي المقترحة من قبل الأدبيات ذات الصلة والتي اعتبر تأثيرها مهماً على مخاطر الائتمان. لتحقيق هدف الدراسة تمّ بدايةً اختبار استقرارية السلاسل الزمنية للمتغيرات المختارة، ومن ثم اختبار وجود علاقة طويلة الأجل بين المتغيرات التفسيرية والمتغير التابع باستخدام نموذج الانحدار الذاتي للفترات الموزّعة (ARDL)، وأخيرا تمّ اختبار الأثر المحتمل لمتغيرات الدراسة على مخاطر الائتمان باستخدام نموذج بانل للآثار الثابتة Fixed Effect Model. تظهر النتائج أنّ متغيرات الاقتصاد الكلي لها دور كبير في تفسير التغيرات الحاصلة في جودة محفظة القروض والتي تسبب ارتفاع نسب الديون غير العاملة في المصارف التجارية السورية. حيث تبين وجود أثر سلبي ومعنوي لكل من معدل النمو في الناتج المحلي الإجمالي الحقيقي ومعدل التضخم على مخاطر الائتمان، بينما وجود أثر إيجابي ومعنوي لكل من سعر الفائدة الحقيقي وسعر الصرف الحقيقي الفعّال على مخاطر الائتمان.